Employment regulation and labor market policy in Germany, 1991 - 2005 - Bernhard Ebbinghaus; Werner Eichhorst (Institute for the Study of Labor (IZA), 2006)
The paper provides an overview of institutional provisions and reforms regarding employment protection, active and passive labor market policies in Germany as well as of actors' responsibilities in these areas. It covers the period between the early 1990s and the most recent Hartz reforms. Empirical data on labor market outcomes with respect to the levels and structures of both employment and unemployment complements this study.
urn:nbn:de:101:1-2008050986
Keywords: 330